GENERATION RATES AND CHARACTERIZATION OF ORDINARY SOLID WASTE IN FOUR MUNICIPALITIES OF THE METROPOLITAN AREA COSTA RICA - Herrera-Murillo, Jorge (2016)
Generation rates and the characterization of ordinary solid waste were determined in the residential and commercial sectors of four municipalities in the Metropolitan Area of Costa Rica. For this, a sampling was performed on a representative number of homes and businesses in the 2014-2015 period during seven days. The waste generation weighted average rate in the work area turned out to be 0.59 kg / inhabitants.-day. Solid waste generated presented as major components: organic 55.9%, followed by materials with high potential to be recycled or used as fuel (10.2% plastic, paper and cardboard 10.4%). The average moisture content in the waste was 58.7 mass% (minimum 54% in Alajuela and maximum 63% in Barva), of which up to 67% may be attributable to biodegradable organic waste. The average waste volumetric weight was 155 kg / m3 (minimum of 141 in Belen and maximum of 163 in San Jose). Significant differences appear in the composition of commercial and residential waste, mainly regarding organic waste, paper, cardboard, and plastic.